Effectiveness of Liability Exemption Clause Regulations in Standard Agreements Based on Law Number 8 Of 1999 Concerning Consumer Protection - Shindy, Felicia; Djajaputra, Gunawan (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Standard agreements are common instruments in modern transactions, whether in the service, trade, or digital services sectors. However, the use of liability exemption clauses by business actors in these agreements often creates an imbalance between business actors and consumers. This study aims to analyze the legal provisions regarding liability exemption clauses based on Law Number 8 of 1999 concerning Consumer Protection (UUPK) and assess the effectiveness of its implementation in providing proportional legal protection for consumers. The research method used is a literature study by examining relevant laws and regulations, law books, academic articles, and court decisions. The results of the study show that normatively, the UUPK, particularly Article 18, explicitly prohibits the inclusion of standard clauses that limit, transfer, or exempt the liability of business actors. This prohibition is imperative, and any clause that contradicts it is declared null and void. However, the effectiveness of this regulation in practice still faces various obstacles, including low consumer awareness, weak supervision, and rampant violations in digital transactions. Nevertheless, the existence of the UUPK remains an important legal basis in efforts to enforce consumer rights and resolve disputes through litigation and non-litigation channels. Therefore, it is necessary to strengthen supervision, improve business compliance, and educate consumers to ensure that the protection guaranteed by the UUPK is optimally realized.